Experimental and simulation method of introducing compressive residual stress in ASTM A516 grade 70 steel - Isa M.R.; Sulaiman S.N.; Zaroog O.S. (Trans Tech Publications Ltd, 2023)
Shot peening; Stress analysis; Surface treatment; 70 steel; Compressive residual stress; Multi-shots; Simulation procedures; Single shots; Surface of materials; Tensile loading; Residual stresses